Editor's Choice – Endovascular Repair Versus Surgical Repair for Japanese Patients With Ruptured Thoracic and Abdominal Aortic Aneurysms: A Nationwide Study. (June 2019) - Yamaguchi, Tetsuo; Nakai, Michikazu; Sumita, Yoko; Nishimura, Kunihiro; Tazaki, Junichi; Kyuragi, Ryoichi; Kinoshita, Yoshihisa; Miyamoto, Takamichi; Sakata, Yasushi; Nozato, Toshihiro; Ogino, Hitoshi
Abstract : Objective: This study compared outcomes after endovascular aneurysm repair (ER) and open surgical repair (OR) of ruptured descending thoracic aortic aneurysms (rDTAA) and ruptured abdominal aortic aneurysms (rAAA) through a nationwide analysis performed in Japan. Methods: This was a national registry based retrospective comparative study using data from the Japanese Registry of all Cardiac and Vascular Diseases Diagnostic Procedure Combination (JROAD-DPC) database, a nationwide claim based database from more than 600 hospitals. Patients admitted to certificated teaching hospitals with rDTAA and rAAA and treated by either ER or OR between 1 April 2012 and 31 March 2015 were identified. A propensity score matched analysis was performed to compare ER and OR. Results: About 40% of the total cohort ( n  = 8, 302) were managed conservatively for various reasons, including limited options in primary care facilities in certain areas. In total, 983 patients had rDTAA (OR = 511; ER = 472) and 2, 320 (OR = 1, 754; ER = 566) had rAAA. Altogether, 604 and 1, 080 patients were matched with rDTAA and rAAA, respectively. Compared with OR, ER was associated with significantly better in hospital mortality in patients with rDTAA (ER = 22.5%; OR = 29.8% [ p  < .001]) and similar mortality for those with rAAA (ER = 25.7%; OR = 24.3% [ p  = .57]). ER involved significantly shorter hospital stays for rDTAA (ER = 25.5; OR = 32 days [ p  < .001]) and rAAA (ER = 16; OR = 21 days [ p  < .001]). The median Barthel Index at discharge was ≥75/100 for all groups, and there were no differences between ER and OR. Total medical costs were significantly lower for ER for rDTAA (ER = ¥6.47 million, OR = ¥7.28 million [ p  < .001]) but were higher for rAAA (ER = ¥4.65 million; OR = ¥3.43 million [ p  < .001]). Conclusion: A Japanese nationwide observational study showed that in hospital outcomes for ER vs. OR were more favourable for rDTAA and comparable for rAAA. ER resulted in an equivalently favourable functional status at discharge and significantly shorter hospital stays.